An Exploratory Study of Students Perceptions of Using ChatGPT in Undergraduate Thesis Writing - Riswan Septriayadi Sianturi; Andi Reza Perdanakusuma; Nur Aini Cahyati (International Journal of Education and Learning, 2025)
ChatGPT, an artificial intelligence-based technology developed byOpenAI, exhibits remarkable capabilities in addressing a wide range ofinquiries and has emerged as a transformative tool in the realm ofscientific research. Despite its potential, the extent to which ChatGPTcan assist undergraduate students in thesis writing remainsunderexplored. This study seeks to investigate students#39; perceptionsregarding the utilization of ChatGPT in the process of undergraduatethesis composition. Employing a qualitative research methodology, datawere collected through semi-structured interviews with students fromthe Faculty of Computer Science at Universitas Brawijaya. Thematicanalysis was utilized to examine the data, revealing a spectrum ofstudent perspectives on the application of ChatGPT in thesis writing.While students acknowledge that ChatGPT enhances writing efficiencyand improves work quality through its various capabilities, they alsorecognize its limitations, particularly concerning the accuracy andreliability of information. Moreover, students express concerns aboutthe potential for over-reliance on ChatGPT, which could impede thedevelopment of creativity, research skills, and critical thinking.